Strategic plan of the IFPRI program on fragile and conflict-affected food systems (FCAS): 2026-2029 - Kosec, Katrina; Ambler, Kate; Abay, Kibrom; Carrillo, Lucia; Gilligan, Dan (International Food Policy Research Institute, 2025)
Humanitarian crises are becoming more frequent, protracted, and complex. Fragility, conflict, climate extremes, and displacement increasingly converge to undermine food security, disrupt livelihoods, and erode community resilience across dozens of countries. In these settings, humanitarian actors face enormous pressure to deliver assistance in ways that are timely, inclusive, accountable, and aligned with the needs and priorities of affected populations. Further, governments demand evidence on what policies, programming, and other investments can support prevention, recovery, and resilience. In the current funding environment, global humanitarian financing is stretched thinner than ever, making improvements in effectiveness, efficiency, and quality of humanitarian actions all the more urgent.